Perceptions of High School Head Teachers about Improving the High School Teachers Performance through High-Performance Work System - Shamsa Parveen, Shamim Haider Tirmizi (JCTE, 2023)
The present study focused on the school heads’ perceptions for the improvement of school teachers’ performance keeping in view the highperformance work system (HPWS), a strategy of Human ResourceManagement (HRM) for performance improvement at the secondary level of education. The high-performance work system is a strategy related to the performance of employees. In Pakistan, at first, people think that a High-Performance Work System (HPWS) strategy is specific only to the business organizations. However, now it is proved through different empirical studies that High-Performance Work System (HPWS) is helpful to all types of organizations and especially in educational institutions. The researcher selected six important HPWS strategies selection, training, performance appraisal, compensation, teamwork, and sharing of knowledge to conduct this study. The most important function of HPWS in schools is to enhance teachers’ work. The population of the study comprised of all 174 male and female heads of government high schools of Multan district. 36 head teachers were randomly selected out of which 18 were male and 18 were female head teachers as the sample of the study. This study was descriptive based on a survey. To collect the information from head teachers, a questionnaire with 48 statements was developed after validation 24 statements were finally selected. Data was collected and responses were carefully interpreted. A focus group discussion with three open-ended questions was conducted. 12 school heads were conveniently selected and invited for a focus group discussion. Out of twelve 4 Male and 3 female head teachers participated in the discussion. Major findings of the study showed that the schools having greater mean score were performing better than the the study under research. It was concluded that by improving teachers’ performance, it is possible to bring about a major positive change in the overall performance of schools. It was recommended that the government should pay more attention to HPWS as part of the school department.